PENGARUH PENDEKATAN CTL BERBANTUAN MEDIA MONSTER MATH TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Abdillah, Dania; Hafiziani Eka Putri; Puji Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe the influence of the CTL approach on students' ability to understand mathematical concepts in class III mathematics subjects in one of the elementary schools in North Jakarta City 1. This research uses a quantitative type of research and the method used is the experimental research method. This research uses a quasi-experimental non-equivalent control-group design. The population in this study were all grade III elementary school students in North Jakarta City 1. The samples in this study were grade III C 20 students as the experimental class and grade III A 20 students as the control class. Data collection techniques in this research are tests and non-tests. The instruments in this research consisted of Mathematical Concept Understanding Ability Test. The data analysis techniques in this research are descriptive and inferential analysis to analyze quantitative data. The results of the research show  There is an influence of applying the Contextual Teaching and Learning (CTL) approach assisted by Monster Math media on students' ability to understand mathematical concepts. Furthermore, there was a positive effect of applying the CTL approach, assisted by Monster Math Media, on the math concept understanding ability of students.   Keywords: elementary school, Contextual Teaching and Learning (CTL), math concept understanding ability, monster math media